Assessment of the problems of date palm growers and their possible solutions at Khairpur - Ibupoto, S. A.; Maitlo, W. A.; Memon, S. A. (International Journal of Agricultural Technology, 2015)
The survey of Taluka Kot Diji Khairpur was conducted to assess the problems of date palm growers. A questionare was developed and 60 farmers of Kot Diji were interviewed. The results were analyzed by total number of respondents divided by total number of farmers that interviewed. The date palm growers are facing many problem like no proper credit facilities, no support price of date palm given by the government, no demonstratation of improved production technologies, no market exploitation for date palm export, no access to recent research findings, pre and post harvest aspects of date palm, no Govt processing Industry, no cold storage facility, no guidance on effective and timely control of insects, pests and diseases, shortage of irrigation water, no proper soil and water testing facility, no trainings facilities to farmers and no proper Agriculture extension services to growers and no government support if crop damaged by monsoon rains. The 91.67% farmers suggested the announcement of support price by the government, 73.33% suggested effective dissemination of improved production technologies to growers and 68.33% suggested formation of facilitated extension office for the farmers to get their problems solved. However, among other suggestions came from the growers for Government, Improvement in extension service, monthly coordination meeting with scientists, weekly visit of extension officers, crop monitoring by the extension workers, launching training of grower’s, establishment of storage facilities, training for export quality fruit production and announcement of awards for growers producing good quality fruit of date palm. Facilitate growers with crop inputs for improvement of their socio- economic status, Put Date Palm development on National priority.